Effect of the Family Caregiver Empowerment Model Intervention on the Self-Efficacy of People with Type 2 Diabetes Mellitus - Rondhianto, Rondhianto; Hakam, Mulia; Al Alawi, Rafi Izuddin (Fakultas Ilmu-ilmu Kesehatan, 2025)
Low family support in diabetes management can decrease the self-efficacy of people with type 2 diabetes mellitus (T2DM), impacting diabetes management and outcomes. Healthcare providers can use the family caregiver empowerment model (FCEM) intervention to empower families as caregivers. The study aimed to analyze the effect of the FCEM intervention on people with T2DM self-efficacy. The randomized control trial study was conducted with 85 respondents (intervention group = 41; control group = 44), randomly selected using cluster random sampling. The intervention group received an empowering intervention based on the FCEM model, while the control group received standard care. Sociodemographic and diabetes self-efficacy questionnaires were used to collect the data. Data were analyzed using the dependent t-test and Mann-Whitney U test. The results showed a significant difference in self-efficacy in both groups before and after the intervention (p = 0.001). There was also a significant difference between the intervention and control groups (p = 0.001). The FCEM interventions had a positive effect on the self-efficacy of the people with T2DM. Therefore, healthcare providers can use the FCEM intervention to enhance the family's role in diabetes management and increase the self-efficacy of people with T2DM, improving diabetes self-management and outcomes.